Digital biomarkers for psoriatic arthritis: a qualitative focus group study on patient-perceived opportunities and barriers - Ilja Tchetverikov; Marijn Vis; Marc R. Kok; Jolanda J. Luime; Yvonne P.M. Goekoop-Ruiterman; Wendy Wagenaar; Laura C. Coates; Patty de Groot; Jasper Foolen (RMD Open)
Objectives The widespread adoption of wearables, for example, smartphones and smartwatches in the daily lives of the general population, allows passive monitoring of physiological and behavioural data in the real world. This qualitative study explores the perspective of psoriatic arthritis (PsA) patients towards these so-called digital biomarkers (dBMs).Methods As part of a Design Thinking approach, six focus groups were conducted involving 27 PsA patients. The semistructured topic guide included disease activity, coping strategies, care needs, and potential advantages and disadvantages of dBMs. Thematic analysis followed an abductive coding method.Results PsA daily permeates patients’ lives, both physically and mentally. Participants discussed how their lives are focused on minimising the impact of the disease on their daily routines. Their attempts to gain control over their disease highly depend on trial and error. Flare-ups are related to physiological as well as behavioural micro and macro changes. Understanding these changes could enable the detection of (early) flare. Participants elicited pros and cons of the use of dBMs, discussed their intended use and made practical remarks. This led to three main themes: ‘Perceived dBM opportunities’, ‘Mapping Disease activity’ and ‘Perceived dBM barriers and pitfalls’.Conclusion PsA patients are receptive to dBMs for tracking the disease symptoms. Disease activity is regarded multifaceted and thus, dBMs should include a broad range of features to truly reflect the disease activity status. Reducing the time of trial and error in learning to manage the disease is regarded beneficial. Establishing and maintaining the relationship with their attending physicians is a prerequisite, even if remote patient monitoring becomes an alternative for some physical hospital visits.